2021
DOI: 10.2319/080520-687.1
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary arch development with Invisalign system:

Abstract: Objectives To evaluate tooth movements during maxillary arch expansion with clear aligner treatment. Materials and Methods The study group included 28 subjects (16 females, 12 males, mean age 31.9 ± 5.4 years) collected prospectively from January 2018 to May 2019. Inclusion criteria were European ancestry, posterior transverse discrepancy of 3–6 mm, permanent dentition stage, presence of second permanent molars, mild or moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 29 publications
10
37
0
Order By: Relevance
“…To test the accuracy of ClinCheck planning, measurements taken at T2 were analysed in comparison with outcomes planned for the end of the first phase of aligners (T2CC) with a predictability of 82%. These results agreed with those obtained by other studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], reporting that the ClinCheck prospected a greater distal rotation than realized and which is necessary to provide a further correction of mesial rotation movement during the refinement additional phase.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To test the accuracy of ClinCheck planning, measurements taken at T2 were analysed in comparison with outcomes planned for the end of the first phase of aligners (T2CC) with a predictability of 82%. These results agreed with those obtained by other studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], reporting that the ClinCheck prospected a greater distal rotation than realized and which is necessary to provide a further correction of mesial rotation movement during the refinement additional phase.…”
Section: Discussionsupporting
confidence: 92%
“…Plenty of investigations [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] stated a high percentage of mesial-rotation of upper first molars in Class II malocclusion. In 2019, de Oliveira-Viganò et al stated that dental Class II show the highest levels of mesio-palatal rotation of the upper first molars [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the expansion movements, recently, Lione et al [21] found a high predictability of the planned molar expansion with CA in permanent dentition. Our results showed that the same accuracy could be obtained in mixed dentition as well.…”
Section: Discussionmentioning
confidence: 99%
“…With the significant recent improvements in computer-aided design/computer-aided manufacturing (CAD/CAM) and dental materials, there has been an increase in the demand for plastic systems [2]. Clear aligners provide an esthetic and comfortable treatment experience, facilitate oral hygiene, cause less pain as compared to fixed orthodontic appliances, and reduce the number and duration of appointments [3][4][5]. The aligner therapy also involves a lower incidence of demineralization, enamel abrasion, periodontal lesions, and mucosal irritations [6].…”
Section: Introductionmentioning
confidence: 99%